Optimizing and real-time control of biofilm formation, growth and renewal in denitrifying biofilter. (June 2016) - Liu, Xiuhong; Wang, Hongchen; Long, Feng; Qi, Lu; Fan, Haitao
Graphical abstract: Highlights: Optimizing and control of biofilm was studied in biofilter (600 m 3 /d). Biofilm formation, growth and removal can be controlled using turbidity. The filter layer status can be indicated by Turb break points on turbidity profile. Filter layer clogging coefficient can be used to determine filter layer condition. Abstract: A pilot-scale denitrifying biofilter (DNBF) with a treatment capacity of 600 m 3 /d was used to study real-time control of biofilm formation, removal and renewal. The results showed biofilm formation, growth and removal can be well controlled using on-line monitored turbidity. The status of filter layer condition can be well indicated by Turb break points on turbidity profile. There was a very good linear relationship between biofilm growth degree ( X biof ) and filter clogging degree ( C filter ) with R 2 higher than 0.99. Filter layer clogging coefficient (Yc) lower than 0.27 can be used to determine stable filter layer condition. Since variations of turbidity during backwash well fitted normal distribution with R 2 higher than 0.96, biofilm removal during backwash also can be well optimized by turbidity. Although biofilm structure and nirK -coding denitrifying communities using different carbon sources were much more different, DNBF was still successfully and stably optimized and real-time controlled via on-line turbidity.